USABILITY TESTING OF SIFINAS DIGITAL APPLICATION DEVELOPMENT AND ITS EFFECT ON USER SATISFACTION AND MANAGERIAL PERFORMANCE - Pristiyono, Pristiyono; Suryadi, Sudi; Syahfii, Muhammad; Amelia, Reza Rizki (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2025)
The development of the SIFINAs digital application aims to increase the credibility of MSMEs in the financial management of these MSMEs so that they can control their financial transactions or reports more updated, effective and efficient. The purpose of this study was to test the SIFINAs digital application and to determine its effect on user satisfaction and MSME performance. Overall, there were respondents who stated that they were not willing to respond to the research questionnaire so that the data collected was obtained as many as 37 respondents. The results of the study found that the development of the SIFINAs digital application model is one of the simple and simple application models that greatly supports the performance of MSMEs. The results of testing the research hypothesis show that the development of WEB-based applications affects user satisfaction, user satisfaction affects MSME performance and WEB-based application development affects MSME performance. In the future, the SIFINAs digital application that is being developed is feasible to be used or implemented en masse by medium-level business actors